2006
DOI: 10.1016/j.virol.2006.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Human coronavirus OC43 infection induces chronic encephalitis leading to disabilities in BALB/C mice

Abstract: The notion that an infectious respiratory pathogen can damage the central nervous system (CNS) and lead to neurological disease was tested using a human respiratory coronavirus, the OC43 strain of human coronavirus (HCoV-OC43). First, primary cell cultures were used to determine the susceptibility of each type of neural cells to virus infection. Neurons were the target cells, undergoing degeneration during infection, in part due to apoptosis. Second, neuropathogenicity was investigated in susceptible mice. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(211 citation statements)
references
References 66 publications
3
200
0
8
Order By: Relevance
“…HCoV-OC43, a respiratory CoV, could be a powerful tool for gaining new insights into the neurological manifestations and neurotropic mechanisms of other respiratory viruses. In the present study, our data demonstrated that rOC43-ns2DelRluc levels reflected HCoV-OC43-WT replication in the brain and its spread to the spinal cord of living mice, with bioluminescence intensity directly correlating with viral loads as measured by IFA and western blot and consistent with previous studies (Dubé et al, 2018;Jacomy et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HCoV-OC43, a respiratory CoV, could be a powerful tool for gaining new insights into the neurological manifestations and neurotropic mechanisms of other respiratory viruses. In the present study, our data demonstrated that rOC43-ns2DelRluc levels reflected HCoV-OC43-WT replication in the brain and its spread to the spinal cord of living mice, with bioluminescence intensity directly correlating with viral loads as measured by IFA and western blot and consistent with previous studies (Dubé et al, 2018;Jacomy et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…CoVs, which cause respiratory diseases, have also been associated with neurological complications (Arabi et al, 2015;Arbour et al, 2000;Burks et al, 1980;Hung et al, 2003;Netland et al, 2008), with HCoV-OC43 even causing fatal encephalitis (Jacomy et al, 2006;Jacomy and Talbot, 2003;Morfopoulou et al, 2016); however, the mechanisms responsible for their dissemination and penetration in the host CNS remain unclear. Therefore, easily observable, living animal models are required to identify the mechanisms of HCoV infection in the CNS and enable the development of antiviral drugs for treating and preventing CoV infection and their associated severe CNS pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also direct evidence for involvement in enteric (e.g. strain HECoV 4408) (Zhang et al, 1994;Zhu et al, 2006) and suggestive evidence for involvement in neurological disease (Clarke et al, 1979;Flewett et al, 1987;Foley and Leutenegger, 2001;Gerna et al, 1985Gerna et al, , 1984Han et al, 2006;Jacomy et al, 2006;Luby et al, 1999;Resta et al, 1985;Saif, 2004;Schnagl et al, 1990Schnagl et al, , 1986Sitbon, 1985;Vabret et al, 2006;Zhu et al, 2006). HCoV are frequent causes of the common cold; usually a self-limiting upper respiratory tract (URT) illness (Heikkinen and Jarvinen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Virus was propagated and titrated on Vero cells as described previously (Lymberopoulos & Pearson, 2007). Primary embryonic neurons were harvested from E16-18 CD-1 mice (Jacomy et al, 2006). LA-N-5 cells were maintained and differentiated with RA (Hill & Robertson, 1998).…”
Section: Methodsmentioning
confidence: 99%